Greening organizations through the leaders' influence on positive deviance in corporate environmental reporting practice: A case of Malaysian public listed company - Jaaffar; Hisham A.; Amran; Azlan (Serials Publications, 2023)
The main aim of the present study is to determine the role of environmentally expert and experience leader on positive deviance behaviour in corporate environmental reporting practices. Based on the environmental reporting index develop based on the concept of positive environmental deviance, the study measured positive deviance behaviour in environmental reporting practices of 209 Malaysian public listed companies based on 5 years panel data. It was found that environmental expert and experience board of directors have a positive significant relationship with positive deviance in environmental reporting practices. Nevertheless it have been found that there were no significant relationship between environmentally expert and experience CEO and its interaction effect with environmentally expert and experience board of directors on positive deviance behaviour in environmentally reporting practices. This study conceptualized positive deviance behaviour in environmental reporting practices as the strategic behaviour of the corporations to improve the impact of environmental sustainability practices beyond the required regulations by disclosing set of information regarding to their proactive management practices and performance which: (1) exceed minimal norms; (2) deviate from others within the field; (3) go beyond what is required by regulation; and (4) associated broader scale changes. 2017 Serials Publications Pvt. Ltd.